تطبيق المرمز المسبقX and Y Precoder في أنظمة الهوائيات المتعددة MIMO بإضافة قناة راجعة محدودة - غدير ماضي; رزان حبيب (Tishreen University, 2017)
شهدت السنوات الأخيرة نمواً كبيراً في الاتصالات اللاسلكية نتيجة طلب المستخدمين معدلاتعالية لنقل المعطيات. ومن هنا جاء الحافز لتطبيق أنظمة MIMOفي العديد من التقنيات والمعايير الحديثة؛ لتأمين معدلات نقل المعطيات المطلوبة. لكن لسوء الحظ هذه الأنظمة حساسة تجاه ظروف الإرسال السيئة مثل الخفوت. تستطيع عملية الترميز المسبق Precoding تحسين أداء أنظمة MIMO لتتلاءم مع شروط القناة المتغيرة، من خلال معرفة معلومات حالة القناة CSI بشكلٍ تام بالمرسل. لكن الحصول على هذه المعلومات بشكلٍ تام في المرسل غير قابل للتطبيق العملي؛ بسبب حجمها الهائل، لذا لابد من تخفيض حجمها عبر عملية تعرف بالتكميم، وإرسالها عن طريق قناة راجعة محدودة. إن تقنية X and Y Precoderهي إحدى تقنيات الترميز المسبقالتي تمت دراستها بافتراض معلومات حالة القناة كاملة لدى المرسل. سنقوم في بحثنا هذا بإضافة قناة راجعة محدودة إلىهذه التقنية لتصبح قابلة للتطبيق العملي، حيث أظهرت النتائج أن خسارة أداء X and Y Precoder بوجود قناة راجعة محدودة مقبولة نوعاً ما. Recent years have witnessed a significant growth in wireless communication as a result of user demand on high rates of data transmission. Therefore, there is a great motivation for the application of MIMO systems in many modern communication standards in order to provide the required data transmission rates. Unfortunately, these systems are sensitive to poor transmission conditions such as fading. Precoding can improve the performance of MIMO systems to adapt with channel conditions by knowing the full channel state information (CSI) at the transmitter. However, a full CSI is often unrealistic in practice because of the huge amount of this information to be sent back. Therefore, this information must be reduced and sent through a limited feedback channel. X and Y Precoder are one of the precoding techniques that have been studied assuming a full CSI at the transmitter. In this research, we will add a limited feedback channel to this technique in order to become applicable in practice. The result has shown that the loss of performance by adding a limited feedback channel may be acceptable.